2017
DOI: 10.1016/j.resconrec.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Battery pack recycling: Behaviour change interventions derived from an integrative theory of planned behaviour study

Abstract: Belgium has passed the 45% cap, mandated by the European Union, by achieving a collection rate of over 50% in 2012. Having such a collection rate, Belgium is amongst the frontrunners in battery recycling in Europe. However, despite the efforts, about 40% of used batteries are still not properly collected. Particularly troublesome according to the national producer responsibility organization are the battery packs. In this paper we therefore investigate the drivers and barriers to battery pack drop-off intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 103 publications
10
55
1
2
Order By: Relevance
“…Many studies have reported a positive and significant effect of attitudes on human behavior (Masud et al, 2015;Afroz et al, 2013). In contrast, some studies also report that attitudes do not significantly affect intention (Dixit and Badgaiyan, 2016;Lizin et al, 2017;Wan et al, 2014). Based on the literature sought in this study, the following hypothesis was put forward:…”
Section: Previous Studies On Recycling Behaviormentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies have reported a positive and significant effect of attitudes on human behavior (Masud et al, 2015;Afroz et al, 2013). In contrast, some studies also report that attitudes do not significantly affect intention (Dixit and Badgaiyan, 2016;Lizin et al, 2017;Wan et al, 2014). Based on the literature sought in this study, the following hypothesis was put forward:…”
Section: Previous Studies On Recycling Behaviormentioning
confidence: 94%
“…Singh et al (2018) denote a subjective norm as a mixture of prohibitive and descriptive norms that follow the perception of satisfactory/unsatisfactory behavior by interactive relationships and neighboring societies. Many researchers report that household subjective norms and intentions were significantly and positively related (Echegaray and Hansstein, 2017;Lizin et al, 2017). Based on these views, the following was suggested:…”
Section: Previous Studies On Recycling Behaviormentioning
confidence: 99%
“…20 Therefore, steering behavioural changes, such as through choice architecture, could prove helpful. We do have evidence from other strategies on waste (eg e-waste or food waste) that consumers may be responsive to perceived behavioural control, 21 recycling convenience 22 and the possibility of surplus redistribution. 23 Such strategies should be (experimentally) tested for usability and effectiveness with respect to household pharmaceutical waste.…”
Section: Suggestionmentioning
confidence: 97%
“…In the last three decades, behavioral scientists increasingly turned their attention to the research of pro-environmental behavior, trying to explain it by means of experimental studies or surveys all over the world: Africa [20], South-America [21], Asia [22,23] or Europe [24,25], from various perspectives: targeting students [26] and households [27] or workplace behaviors [28].…”
Section: Theories Explaining People's Behaviors Particularly In Wastmentioning
confidence: 99%